Diversity of common bean rhizobia in blackland of northeastern China and their symbiotic compatibility with two host varieties - Wang, Ziqi; Liu, Lili; Hu, Dong; Wang, En Tao; Gu, Chuntao; Wang, Hao (Frontiers in Microbiology, 2023)
Common bean (Phaseolus vulgaris L.) is an important crop in the world that forms root nodules with diverse rhizobia. Aiming to learning the rhizobial communities associated with common bean in the black soil of Northeast China, 79 rhizobia were isolated from root nodules of two host varieties (Cuican and Jiadouwang) grown in two sites of blackland, and were characterized by comparative sequence analyses of 16S rRNA, recA, atpD, nodC, nifH genes and whole genome. As results, Rhizobium indigoferae, R. anhuiense and R. croatiense as minor groups and three dominant novel Rhizobium species were identified based on their ANI and DDH values to the type strains of relative species. This community composition of rhizobia associated with common bean in the tested black soils was unique. Despite their different species affiliation, all of them were identified into the symbiovar phaseoli according to the phylogenies of symbiotic genes (nodC and nifH). While the discrepancies found in nodC and nifH genotypes evidenced that the evolutions of nodulation (nod) and nitrogen fixation (nif) genes were partially independent. In addition, only one dominant rhizobial species was shared by the two common bean varieties grown in the two soil samples, implying that both the plant variety and the soil characters affected the compatibility between rhizobia and their hosts. These findings further enlarged the spectrum of common bean-nodulating rhizobia and added more information about the interactions among the soil factors, rhizobial species, and host plants in the symbiosis.